Enhanced breakdown strength and improved ferroelectric properties in lead-containing relaxor ferroelectric ceramics with addition of glass. (4th October 2019) - Jin, Li; Pang, Jing; Luo, Wenting; Huang, Yunyao; Jing, Ruiyi; Xu, Jie; Guo, Dong; Hu, Qingyuan; Tian, Ye; Lu, Xu; Wei, Xiaoyong; Gao, Feng
Abstract: Relaxor ferroelectrics (RFEs), which possess high maximum polarization ( P max ), low remnant polarization ( P r ) and coercive field ( E c ), are good candidates for the applications in electrostrictive devices. Compared to lead-free RFEs, lead-containing RFEs possess higher P max, due to the contribution by lead ions. However, relatively low breakdown strength (BDS) in lead-containing RFEs becomes a bottleneck for exploring the electrostrictive properties especially at higher electric field. In this work, we synthesized (1− x )[0.5573Pb(Mg1/3 Nb2/3 )O3 -0.4427PbTiO3 ]- x Ba(Zn1/3 Nb2/3 )O3 [(1− x )PMNT- x BZN, x  = 0.1725, 0.1925, 02125 and 0.2325] RFE ceramics with addition of Li2 O-B2 O3 -SiO2 glass additives (2 wt%) and studied the BDS and dielectric/ferroelectric properties in detail. It was found that an enhancement of BDS from ∼120 kV cm −1 for undoped samples to ∼160 kV cm −1 for glass-doped samples. Higher P max, lower P r and lower E c were simultaneously obtained in x  = 0.1725, 0.1925 and 02125 compositions, suggesting improved ferroelectric properties. Purely electrostrictive strains with levels from 0.147% to 0.069% were obtained in glass-doped compositions when x increases from 0.1725 to 0.2325 at 30 °C, and more than 40% strain response were maintained when temperature is increased to 130 °C. This work proves the effectiveness of glass additives to enhance BDS and improve ferroelectric properties in lead-based (1− x )PMNT- x BZN RFE ceramics.